New tools in luxury brand communication and their impact on the purchase intention in luxury - Duška, David (2025)
This thesis examines new tools in luxury brand communication and their impact on the purchase intention in luxury. Using research model based on the theory of planned behavior, the factors of attitudes, subjective norms and perceived behavioral control are tested and their impact on purchase intentions of Generation Z and Generation Y consumers of digital luxury assets is examined. Main insights highlights are that all three factors have relevance in the process of creation of the purchase intention. The data examined was gathered using quantitative questionnaire. The results of the research could help the luxury brands to understand the reasoning behind purchase intention of the selected target group and provide solid data for creating their marketing strategies.